Arrians "Indiké" : Eine Untersuchung der Darstellungstechnik - Schunk, Henning (Philippika, 2019)
In the second century AD Flavius ​​Arrianus wrote a history of Alexander the Great. (anabase); This he joined a dichotomous work on India (Indiké), in which he connected geographical and ethnographic information (Ekbolé) with the description of the naval voyage of Nearchus (Paráplous). Arrianus states that he follows in his work the (now no longer preserved) journey report that Nearch had written about 500 years earlier about his journey from India to Mesopotamia on behalf of Alexander. For this reason, among other things, the journey report was viewed in the modern age as Nearch's work, which Arrian adopted more or less verbatim in his writing. In his philological and literary study, Henning Schunk turns against this compilation thesis and sheds light on the question of the originality of the writing and the associated way in which Arrian dealt with his sources. For this purpose, the study compares Arrian's literary techniques in the paráplous of the Indiké - in which, of course, the ekbolé also plays a role again and again - with the literary character of his anabasis. In this way it can be shown that the Paráplous is also a literary composition by Arrian. Schunk interprets, among other things, according to the principle of 'close reading', shows intertextual references, gives consideration to the target group and the literary genre and asks about the author's intentions. By working out the references to Herodotus, Thucydides, Xenophon and Homer contained not only in the Anabasis but also in the Indiké, Schunk can also show that Arrian also consciously places himself in historiographical traditions with this work.